GEOSPATIAL ASSESSMENT OF VEGETATION CONDITION PRE-WILDFIRE AND POST-WILDFIRE ON LUŠTICA (MONTENEGRO) USING DIFFERENCED NORMALIZED BURN RATIO (DNBR) INDEX - Vujović, Filip; Nikolić, Gojko (Bulletin of Natural Sciences Research, 2022)
Wildfire is one of the most dangerous environmental stressors in most vegetation zones worldwide. Determining and monitoring this stressor is important because of the disturbances that occur during the burning of biomass in ecosystems, as well as because of the damage or suffering of organisms. In the last decade, a greater number of wildfires and burnt areas were recorded in Southern Europe and Montenegro. Therefore, it is important to develop optimal methodology and models to help in better management of forest protection against wildfire. The spatial component in firefighting plays a significant role in management. In this context, Remote Sensing and Geographic Information Systems (GIS) come to the fore, which analyze spatial data and turn it into useful information - models applied in practice. The study aims to geospatial assess condition of vegetation pre-wildfire and post-wildfire in study area of the Luštica peninsula in Montenegro during the summer of 2017. Open and publicly available Sentinel 2 satellite was used. The scaled index differenced Normalized Burn Ratio (dNBR) of burned vegetation was applied as an indicator for assessing the state of vegetation after a wildfire in the open source software Quantum GIS (QGIS). The results of the damage assessment of the burned area based on the applied scaled index reveal that the category of low severity occupies an area of 335.86 ha (7%), moderately-low severity 250.13 ha (5%), moderately-high severity 406.22 ha (8%), high severity 238.03 ha (5%). The unburned areas occupy an area of 3624.95 ha (75%). This study contributes to assessing vegetation conditions and other accompanying activities pre-wildfire and post-wildfire using modern open-source geospatial tools.
Keywords: Wildfire; GIS; Remote sensing; Burned vegetation; Montenegro